Quest for Feminist Technology: Challenges to 21st Feminism - Putri, Perdana (Yayasan Jurnal Perempuan, 2016)
As world develops toward a digital and informational society, feminism finds its place in challenging situation. Numbers of women involved in STEM (Science, Technology, Engineering and Math) are progressively increasing in 21st century. However, the questionremains whether this rising number has significant impact for feminist movement in science, knowledge, and technology. The development of science and technology, foreseeably enough, is quite inimical to feminism1. Using epistemological feminist approach, this paper aims to analyze the contemporary problem of feminism in technology, how its discourse needs to be more developed and critically assessed. I find that feminism needs to broaden its critics not only in term of social-political practice of women in technology, but also it needs to establish its own bodily knowledge in seeking for so-called feminist technology.